2014
DOI: 10.2169/internalmedicine.53.2111
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Gastroenteritis Complicated with <i>Helicobacter pylori</i> Infection Unresponsive to Eradication Therapy

Abstract: An adolescent girl presented with inappetence. Upper gastrointestinal endoscopy showed rough and cracked mucosa at the gastric antrum with a scarred duodenal ulcer, and a biopsy sample demonstrated abundant eosinophils. We therefore diagnosed the patient as having eosinophilic gastroenteritis. Eradication therapy for Helicobacter pylori (H. pylori) did not improve her symptoms; however, proton pump inhibitor therapy was effective in resolving her chief complaints. There are several reports of eosinophilic gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Discoloration and white granular elevations may represent eosinophil accumulations like white exudates in EoE. A few studies have reported cracked mucosa in patients with EGE [26,28]. Magnifying narrow-band image endoscopy showed that cracks were defects of surface mucosal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Discoloration and white granular elevations may represent eosinophil accumulations like white exudates in EoE. A few studies have reported cracked mucosa in patients with EGE [26,28]. Magnifying narrow-band image endoscopy showed that cracks were defects of surface mucosal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports regarding EGIDs complicated by H. pylori infection (Papadopoulos et al 2005;Nakamura et al 2014). H. pylori eradication may or may not be effective for EGIDs, and effectiveness is not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, when the mucosa is in the primary inflammatory location, stomach ache, diarrhoea and/or weight loss are often noted. If the muscular layer is involved, nausea, vomiting and/or stomach ache may be the symptoms 1. EA is common when the serosa is involved, and is probably the most unusual and rare presentation of EG 4 7…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest a role of various cytokines, such as interleukin 3 and 4, granulocyte macrophage colony-stimulating factor and eotaxin, which are produced by eosinophils. Some studies also advocate that food allergens may play a role in local recruitment of eosinophils 1 4…”
Section: Discussionmentioning
confidence: 99%